ASSESSING FAMILY CAREGIVER PREPAREDNESS: COMPETENCIES FOR THE CAREGIVING ROLE. (11th November 2018) - Harvath, T A; Archbold, P G; Stewart, B; Mongoven, J; Bettega, K
Abstract: In early 2015, AARP conducted a national survey of family caregiving and identified that many family caregivers struggle with tasks that nurses typically perform, referred to as "medical/nursing tasks." Many of these family caregivers report feeling ill-prepared for their role. We developed a set of family caregiver competencies based on the work of Archbold & Stewart (1995) in order to provide a framework to assess family caregiver preparedness for the caregiving role. The domains include: Household Management; Personal Care; Mobility; Surveillance; Emotional and Social Support; Health Care Coordination; Complex Nursing Care; Surrogacy; and Stress Management. These domains and associated tasks were subjected to a validation process using a modified Delphi approach. These competencies can be used to develop tools and resources to assess and support caregivers' preparedness to provide culturally appropriate care that reflects the care recipient's values, preferences and goals of care.